The Impact of Smartphone to Literature Education by Kurnia Sakti - Sakti, Kurnia ((JELE) Journal Of English Language and Education, 2021)
Technological advances in this digital age have expanded the use of electronic media, smartphones for teenagers. Smartphones perform the basic functions of communication. Find remote and general information on the Internet. In addition, for young people who are still in school age, the advent of the smartphone is only improves the quality of education positively.